KINERJA APARATUR PEMERINTAHAN DESA TAMBAK REJO KECAMATAN KREMBUNG KABUPATEN SIDOARJO DALAM PELAYANAN E-KTP - Eric Kartika Sari; Ahmad Riyadh U.B (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the performance of village government officials in providing E-KTP services in Tambak Rejo Village, Krembung Sidoarjo District. This research method uses descriptive qualitative. The type of data used in this study is qualitative data, which is divided into two, namely secondary and primary data. Data collection techniques are carried out by reviewing legislation, interviews and observations. Data analysis techniques using data reduction, data presentation and drawing conclusions. The technique of taking informants in this study used a purposive sampling technique. The performance of government officials in village E-KTP services is the focus of this research. Sources of data obtained from interviews and observations. The results of this study indicate that the performance of village government officials in the E-KTP service in Tambak Rejo Village is quite good and optimal. This can be seen from the five indicators which are quite optimal because the understanding of quality, quantity, independence, work commitment and timeliness is quite good.